The Vitality of Balantak Language in a Multilingual Society at Banggai Regency - Valantino A. Pamolango (TALENTA Publisher, 2023)
The primary aim of this paper is to examine the degree of language vitality in the Banggai District by analysing patterns of language usage and intergenerational language transmission within the family domain. Luwuk Banggai serves as the primary hub for educational and commercial activities within the Banggai Regency. The presence of diverse languages in the Banggai Region has resulted in a multilingual society. The Malay Manado language is frequently employed as a lingua franca in addition to the Indonesian language and the three other indigenous languages. The prevalence of these two languages has been contributing to the gradual decline or potential extinction of the Balantak, Banggai, and Saluan languages in the near future. The Balantak Language warrants greater attention due to its relatively small number of speakers in comparison to the two other indigenous languages. This study examines the factors that influence the preservation of local languages within the family domain, as well as the specific areas in which these languages are maintained. Additionally, the obstacles encountered in this preservation process are explored. The research employs a qualitative methodology. The data are acquired by the utilisation of observation, interviews, and document analysis techniques. The present study has identified multiple elements that provide obstacles in the preservation and upkeep of this particular language.